Chimeric proteins consisting of bone morphogenetic protein-2 and a collagen-binding peptide: An in silico analysis - Salma Najmi Dhaniswari; Andi Amanda Artenia Putri; Karina Erda Saninggar; Fumika Abe; Isao Hirata; Koichi Kato (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2026)
Background: To design functional chimeric proteins, the order of connected domains and the insertion of a linker between the domains need to be optimized for the proper folding of individual domains. Purpose: This study aimed to examine the effect of linker lengths and their flexibility, as well as domain arrangements. Methods: Focusing on a chimeric protein consisting of a bone morphogenetic protein-2 (BMP2) domain, a collagen-binding peptide derived from osteopontin (OPNP) or decorin (DECP), and different lengths of flexible (GGGGS)n or rigid (EAAAK)n linkers, the three-dimensional structure of these chimeric proteins was computationally analyzed using AlphaFold2. The predicted structure of the BMP2 domain was compared with the BMP2 reference structure. Root-mean-square deviation (RMSD) was determined between the backbone α-carbons in the predicted and reference structures to assess the structural integrity of the BMP2 domain. Results: The RMSD determined for the BMP2 chimeras decreased by inserting the flexible linkers, with relatively small RMSD in the case of OPNP-(GGGGS)1–4-BMP2 and DECP-(GGGGS)1–2-BMP2. In the case of the rigid linkers, the RMSD was slightly larger than in the case of the flexible linkers. Most of the RMSD values for the chimeric proteins binding to the receptor were smaller than those in the unbound state. Regarding the domain arrangements, a slightly smaller RMSD was observed in the case of N-terminal OPNP or DECP fusion with the flexible and rigid linkers than in the opposite cases. Conclusion: Adding OPNP or DECP at the N-terminus of the BMP2 domain through the flexible (GGGGS)1–3 linker is advantageous for the structural integrity of the BMP2 domain.